STUDENTS' HIGHER ORDER THINKING SKILLS THROUGH INTEGRATING LEARNING CYCLE 5E MANAGEMENT WITH ISLAMIC VALUES IN ELEMENTARY SCHOOL - Kurratul Aini; M Ridwan (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
This study aims to determine the application of learning management learning cycle 5E integrated with Islamic values and how students work in working on HOTS questions after the application of the learning model. The research method used in this research is the descriptive qualitative research method. Observations, interviews, and tests were used in data collection. Observations in the form of teacher observation sheets and student observation sheets. The results of the research at SDN Dungkek I showed that the learning process with the 5E learning cycle model consisted of various activities carried out by teachers with stages of engagement, exploration, explanation, elaboration, and evaluation. In the process, the integration of Islamic values in mathematics subjects with integer material is integrated into moral values , including being patient and sincere, not having evil thoughts, being generous, brave, and always doing good deeds. This study has implications for the importance of managing learning design for teachers to optimize students' potential and strengthen Islamic values.